2022
DOI: 10.1177/00469580221097424
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of Engaged and Recently Married Couples Toward Premarital Screening: A Cross-Sectional Study

Abstract: Background and Objective: Despite that inherited (thalassemia and SCA) and infectious (hepatitis B, hepatitis C and AIDs) diseases and their risk factor consanguineous marriage are widespread among Yemen population, community-based awareness studies towards premarital screening (PMS) is extremely limited, so our study is designed to elicit knowledge and attitude of engaged and recently married couples in Taiz (Yemen) toward PMS. Methods: A cross-sectional study was conducted from April to September 2021 at Tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 35 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…This is in line with previous research that most respondents agreed that premarital screening reduces the incidence of diseases. 26 Women, students in health-related colleges, and a participant's parents' non-consanguineous marriage were all significantly associated with knowledge of pre-marital screening. 27 This study demonstrated that knowledge scores on consanguineous marriage risk and prevention were influenced by age, gender, parental history of consanguinity, family history of consanguineous marriage, and family history of inherited disease.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…This is in line with previous research that most respondents agreed that premarital screening reduces the incidence of diseases. 26 Women, students in health-related colleges, and a participant's parents' non-consanguineous marriage were all significantly associated with knowledge of pre-marital screening. 27 This study demonstrated that knowledge scores on consanguineous marriage risk and prevention were influenced by age, gender, parental history of consanguinity, family history of consanguineous marriage, and family history of inherited disease.…”
Section: Discussionmentioning
confidence: 95%
“…This is in line with previous research that most respondents agreed that pre-marital screening reduces the incidence of diseases. 26 Women, students in health-related colleges, and a participant’s parents’ non-consanguineous marriage were all significantly associated with knowledge of pre-marital screening. 27 …”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations